Nitroxide pharmaceutical development for age-related degeneration and disease - Zarling, Jacob A.; Brunt, Vienna E.; Vallerga, Anne K.; Li, Weixing; Tao, Albert; Zarling, David A.; Minson, Christopher T. (Frontiers in Genetics, 2015)
Nitroxide small molecule agents are in development as preventative or therapeutic pharmaceutical drugs for age-related macular degeneration and cardiovascular disease, which are two major diseases of aging. These aging diseases are associated with patient genetics, smoking, diet, oxidative stress and chronic inflammation. Nitroxide drugs preventing aging-, smoking-, high sugar or high fat diet-, or radiation- and other environmental-induced pathophysiological conditions in aging disease are reviewed. Tempol (TP), Tempol Hydroxylamine (TP-H), and TP-H prodrug (OT-551) are evaluated in (1) nonsmokers versus smokers with cutaneous microvascular dysfunction, rapidly reversed by cutaneous TP; (2) elderly cancer patients at risk for radiation-induced skin burns or hair loss, prevented by topical TP; and (3) elderly smoker or nonsmoker Age-related Macular Degeneration (AMD) patients at risk for vision loss, prevented by daily eye drops of OT-551. The human data indicates safety and efficacy for these nitroxide drugs. Both TP and TP-H topically penetrate and function in skin or mucosa, protecting and treating radiation burns and hair loss or smoking-induced cutaneous vascular dysfunction. TP and TP-H do not penetrate the cornea, while OT-551 does effectively penetrate and travels to the back of the eye, preserving visual acuity and reducing low luminance deficit and night vision loss in dry AMD smokers and non-smoker patients. Topical, oral or injectable drug formulations are discussed.